The Representation of Gender in Emirati Women Novelists Discourse Between 1992 and 2022 - Alrashdi, Mona (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Near & Middle Eastern Studies, 2026)
This dissertation examines the representation of gender in Emirati women’s novels published between 1992-2022, a period that witnessed both the rise of the Emirati novel and rapid social transformation in the UAE. It analyses 26 novels authored by Emirati women, each of which engages with questions of women’s status, rights, and identity in a society negotiating the tensions between state-led modernisation and enduring tribal and familial authority. The study argues that these works provide a sustained critique of patriarchal culture by documenting women’s struggles in both private and public spheres, and by exposing the contradictions between progressive legislation and restrictive social customs. The analysis demonstrates a clear shift in thematic focus across the three decades being focused on. In the 1990s and early 2000s, Emirati women novelists often used fiction as a platform to demand access to education and employment, echoing state narratives that framed women’s participation as central to modernisation. Yet, these themes also revealed the conditional nature of empowerment, as women’s achievements were continually judged against expectations of marriage and family. After 2010, with the sharp increase in literary production, Emirati narratives shifted towards more intimate and socially sensitive concerns. This saw writers begin to foreground issues such as forced and consanguineous marriages, cross-national unions, spinsterhood, divorce, and women’s search for love and fulfilment. This shift unfolded alongside legal reforms in personal status law and debates over custody and citizenship, while tribal and familial authority continued to regulate women’s lives and shape their choices and freedoms. Education and employment, though less central in this later period, remained double-edged; it offered opportunities for autonomy while reinforcing patriarchal anxieties about mixed-gender environments or fields deemed socially inappropriate. Through these themes, Emirati women novelists reveal how women’s lives are simultaneously shaped by state-provided opportunities and enduring social constraints. Their works present the novel as a space of resistance, highlighting the tensions between modernity and tradition. By addressing these woman-centred issues, they effectively shed light on matters that are often marginalised or cannot easily be voiced in public discourse.
APPROVED
Keywords: Emirati women's fiction; Emirati novel; gender representation; gender roles; Arab feminism; local feminism; feminist literary criticism; patriarchy; social norms; social transformation; women's writing; Gulf literature; United Arab Emirates